Principles of risk management and insurance - Rejda, George E (Pearson, 2014)
Principles of Risk Management and Insurance is fully revised to provide current insurance information while maintaining the excellent, broad coverage that has made this text a market leader. Designed for a beginning undergraduate course, this text covers concepts of risk management, legal principles, property and liability insurance, life and health insurance, employee benefits, social insurance, and the functional and financial operations of insurers; Includes bibliographical references and index.